Location-based services handbook : applications, technologies, and security - Ahson, Syed; Ilyas, Mohammad, 1953- (CRC Press, 2011)
Location-Based Services Handbook: Applications, and Technologies, and Security is a comprehensive reference containing all aspects of essential technical information on location-based services (LBS) technology. With broad coverage ranging from basic concepts to research-grade material, it presents a much-needed overview of technologies for positioning and localizing, including range- and proximity-based localization methods, and environment-based location estimation methods. Featuring contributions from field experts around the world, this book addresses existing and future directions of LBS technology, exploring how it can be used to optimize resource allocation and improve cooperation in wireless networks.